Segurança hídrica no Ceará: análise de cenários e de alternativas de intervenção - Rabelo, Udinart Prata (2017)
Drought is a problem that has caused damage to the population of Ceará since its Settlement. Historically the state has suffered from the interannual rainfall variability, Going through several periods of scarcity, which causes lack of water for population consumption, Loss of crops and consequently intense migration. Between the years of 2012 and 2016, the Drought, with precipitation below the historical average during The rainy season, the period of greatest rainfall in the state, with the aggravation of three Of these five were among the ten years with the lowest rainfall observed in Ceará. THE Consequence of this prolonged shortage period was the Reservoirs of the state, main responsible for water maintenance. This fact ignited the The search for new alternatives for the state in drought mitigation that historically On the basis of solutions already used in other countries and those who have been successful Lack of water, including in poor availability and infrastructure The one from Ceará. In this sense, a methodology was adopted to analyze the supply scenarios x Demand, with a study horizon between the years 2020 and 2050, considering the forecasts Of growth of the main demands and the alternatives of offers already used in other Countries that have achieved results. The demands and offers, calculated in billions of meters Were projected and compared year by year between 2020 and 2050, from the Of mitigation alternatives, both for standardized scenarios and for drought scenarios Severe and prolonged dry periods. Complementary to the technical analysis was a Comparison of the implementation costs of each of the alternatives. The combination of these two Generated a ranking of the mitigation alternatives, in order to select the most effective ones And which should focus the state's efforts on investment. The Transposition of São Francisco River and improving the efficiency of irrigation systems presented themselves as The best solutions for water security in the state during the study horizon. O Investment in groundwater, water reuse and demand reduction Populations are of greater importance for future scenarios and for drought situations. Prolonged periods. The desalination of sea water was the alternative with less effect, Mainly because it is still complex and expensive, but also important in Future scenarios. The largest water deficits were found in the final years of each decade.